Mapping women's empowerment to improve family welfare in coastal tourism villages - Komalasari, Yeyen; Sirna, I Ketut; Prasiasa, Dewa Putu Oka (Edelweiss Applied Science and Technology, 2024)
The purpose of this research is to open the insight of all of us those women are potential parties that can be utilized to improve family welfare. Pro poor tourism is a concept in the development of tourist village areas that involve the poor. The selected areas are coastal tourism villages (Serangan-Denpasar Tourism Village, Les-Buleleng Tourism Village, Jasri-Karangasem Tourism Village, Medewi-Jembrana Tourism Village). This research uses an interpretive paradigm which is qualitative research using phenomenology as a methodology. It was found that obstacles to women's empowerment in Pro Poor Tourism, namely increasing women's access to education, health, employment, leadership, and protection from all forms of discrimination and violence. The conclusion is that there needs to be a concrete solution to the obstacles faced in empowering women in the four tourist villages, so that women can be empowered holistically to improve family welfare. Many studies on Balinese women have been conducted where ideally Balinese women are equal to men. But unfortunately, in the four tourist villages studied, none of them entrusted women as managers of tourist villages. The practical implication is that these findings can be considered in the future to see women's empowerment as the spearhead of family and national welfare.